An Observation on Shadowing One’s Own Speech - G, Purushothama; A, Jagadish (Journal of All India Institute of Speech and Hearing)
The process of shadowing involves a subject copying the speaker’s continuous connected speech. Cherry (1953) a tele-communication engineer first noted this phenomenon. He explained phenomenon based on the feedback concepts and emphasised the importance of auditory perception in this process. Marland (1957) applied this method in treating stutterers with the idea that auditory perception might be affected in stutterers. The improvement in the fluency of the shadower was explained by the phenomenon of ’Transfer of auditory perception’. However, the available reports on this aspect of shadowing is scanty. Wingate (1976) reports that there has been little systematic description of subjects speech while shadowing’. Shadow speech is not a faithful copy of ordinary speech as it lacks normal prosody. It is poorly articulated. Sergeant (1961) independently noted that in ’concurrent repetition’ intelligibility scores did not improve beyond 68 per cent even with slower rate and high intensity of speech stimulus. It also happens that shadow substitutes the culture specific equivalents for slightly different words like ’ air-plane ’ for ’ aeroplane ’, he may add words of semantic equivalence.These evidences clearly contradict the idea that shadower’s speech is controlled by a transfer of his auditory perception.